Monitoring Processes in Conference Interpreting: Towards a model for interpreter-trainees / Towards a Monitoring Model for Interpreter-Trainees - Sawyer, David (Meta, 1994)
SummaryMonitoring processes are only one aspect of interpreting; yet, as demonstrated, the misuse of the monitor can lead to an imbalance of efforts, jeopardizing the overall quality of the interpreting. Therefore, a monitor model can serve as a useful tool in interpreting studies. Indeed, interpreter-trainees should be made more aware of monitoring processes involved in language production so that they can use their monitors advantageously while in the booth.